A practical approach to derive heterogeneity index using an integrated petrophysical data analysis - Vali Mehdipour; Ahmad Reza Rabbani; Ali Kadkhodaie (Scientific Reports)
Abstract This study aims to quantify and evaluate various indicators of heterogeneity within the Sarvak reservoir of an Iranian oilfield located in the Dezful embayment (Zagros Basin). The study examined the relationship between the conventional heterogeneity indices and several parameters including residual oil (S_or), the reservoir quality index (RQI), the synthetic velocity deviation log (VDL), as well as the skewness of porosity and permeability, variography and the sorting index derived from the Fullbore Formation Micro Imager (FMI) log. This study demonstrated that the skewness of porosity and permeability can be considered significant indicators of heterogeneity. Furthermore, it was observed that an increase in the range of variography correlates with a rise in the coefficient of variation (CV) of porosity. The findings indicate that VDL and S_or exhibit an inverse relationship with the CV of porosity. Additionally, the sorting index derived from the FMI log serves as an effective indicator of reservoir heterogeneity as it exhibits a high correlation coefficient with the CV of porosity. This study concludes that the introduced indices can effectively characterize the reservoir heterogeneity in the absence of the core data only using the petrophysical logs. Therefore, this study introduces novel indicators to quantify and evaluate heterogeneity in this reservoir, demonstrating that some alternative parameters such as skewness of porosity and permeability, effectively characterize reservoir heterogeneity without using core data.